The Effect of Accounting Information Systems and Work Environment on Employee Performance at the Department of Marine and Fisheries of Central SulawesiProvince in Palu City - Ananda Aulia; Muliati; Tenripada; Mustamin (Journal GoodWill, 2025)
This study examines the effect of Accounting Information Systems (AIS) and the Work Environment on Employee Performance at the Department of Marine and Fisheries of Central Sulawesi Province in Palu City. The research aims to determine whether AIS and the Work Environment, both individually and simultaneously, contribute to variations in employee performance within a public-sector organization. A quantitative approach was employed using a survey method, and data were collected through structured questionnaires distributed to 40 employees selected using purposive sampling. The instrument passed validity and reliability tests, and the data were analyzed using multiple linear regression supported by classical assumption testing. The results reveal that AIS and the Work Environment simultaneously have a significant influence on Employee Performance, indicating that both factors together play a meaningful role in improving performance. However, partial testing shows that AIS has a strong and significant effect on employee performance, demonstrating its essential role in enhancing accuracy, efficiency, and decision-making quality in government operations. Conversely, the Work Environment does not have a significant partial effect, suggesting that existing environmental conditions—although generally conducive—are not sufficiently influential to generate measurable performance changes. These findings highlight the strategic importance of strengthening information system quality and employee capability in system utilization, while improvements to the work environment may require broader structural adjustments to produce significant outcomes.